Al-Sawābiq min al-Asmāʾ fī Kitāb Al-Qirāʾah al-Rashīdah, al-Juzʾ al-Awwal (Dirāsah Waṣfiyyah Taḥlīliyyah) - Muhammad Taufiq fadhlul Rahman (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2015)
Word formation and morphological change in Arabic often result in shifts from the original meaning of a word, giving rise to new lexical meanings. This characteristic contributes to the richness and diversity of the Arabic vocabulary. Among the important morphological elements responsible for such changes are prefixes (sawābiq), which constitute one type of affix and play a significant role in the formation and semantic development of words. Prefixes follow specific morphological rules that help explain how changes in word structure produce semantic modifications or generate new meanings. In addition to other linguistic factors, the attachment of affixes is one of the principal causes of lexical and semantic change in Arabic. This article presents the fundamental theoretical concepts of prefixes in Arabic morphology and analyzes their occurrence in the first volume of Al-Qirāʾah al-Rashīdah. Because the language used in this textbook is relatively simple and accessible for learners of Arabic, it serves as an appropriate source for studying the use and functions of prefixes, thereby facilitating students' understanding of Arabic word formation and meaning.